Muscle Oxygenation during Repeated Cycling Sprints in a Combined Hot and Hypoxic Condition - Yamaguchi, Keiichi; Kasai, Nobukazu; Hayashi, Nanako; Yatsutani, Haruka; Girard, Olivier; Goto, Kazushige (International Journal of Sports Medicine, 2022)
The aim of the present study was to examine the effects of a combined hot and hypoxic environment on muscle oxygenation and performance during repeated cycling sprints. In a single-blind, counterbalanced, cross-over research design, 10 male athletes performed three sets of 3 × 10-s maximal pedaling interspersed with 40-s recovery between sprints under four different environments. Each condition consisted of a control (CON; 20°C, 20.9% FiO2), normobaric hypoxia (HYP; 20°C, 14.5% FiO2), hot (HOT; 35°C, 20.9% FiO2), and combined hot and normobaric hypoxia (HH; 35°C, 14.5% FiO2). Power output and vastus lateralis muscle oxygenation were measured. Peak power output was significantly higher in HOT (892±27 W) and HH (887±24 W) than in CON (866±25 W) and HYP (859±25 W) during the first set (p<0.05). The increase in total hemoglobin during recovery periods was larger in HH than in HYP (p<0.05), while change in tissue saturation index was smaller in HYP than in CON and HOT (p<0.05). The findings suggest that the combination of hot and hypoxia during repeated cycling sprints presented different characteristics for muscle metabolism and power output compared to temperature or altitude stressor alone.
Keywords: heat stress; normobaric hypoxia; environmental stressor; sportsperformance; muscle perfusion